2018
DOI: 10.1007/s40200-018-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in Iranian mothers of children with type 1 diabetes

Abstract: Purpose Having a child with type 1 diabetes as a stressor causes the use of coping strategies in mothers. The aim of this study was to investigate the coping strategies in mothers of children with type 1 diabetes and their relationship with stress management. Methods This study was conducted on mothers of children with type 1 diabetes (N = 180) in Tehran and Karaj (Iran). Data were collected by a multi-sectional questionnaire that its validity and reliability were confirmed. Data were analyzed by SPSS software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In another study was observed that the hemodialysis patients mostly use emotion-focused strategies to cope with the stress (21). Many studies suggest the effectiveness of educational intervention in improving the use of coping styles in different groups and diseases, which are in line with the present study (22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 88%
“…In another study was observed that the hemodialysis patients mostly use emotion-focused strategies to cope with the stress (21). Many studies suggest the effectiveness of educational intervention in improving the use of coping styles in different groups and diseases, which are in line with the present study (22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 88%